Energy saving composite automotive brake rotor prototype - Maleque, Md. Abdul (2013)

(untitled)
Light weight composite materials for automotive application influence on energy saving as well as performance in automotive systems. Brake rotor is identified as a crucial system which halts the kinetic action in vehicles when the situation becomes unsafe due to undesirable conditions. Currently, cast iron is widely used for rotor application but it has been recognized to have a high density, massive and weighty component compared to eco-friendly light weight materials. In this study, a prototype composite brake rotor is fabricated in order to investigate the performance stability and also developed a mathematical model to predict the influence of weight reduction on energy savings. The brake rotor was fabricated using the stir casting technique and the performance test was conducted using a Proton Wira 1.3 brake system rig set up. The result shows that composite brake rotor achieved a weight reduction of about 50% without sacrificing braking performance and 19% energy savings. The friction coefficient of the AMC under different loading is observed to be within the required deviation band for automotive braking system. The thermal response during braking shows that temperature rise for composite rotor is lower with uniform contour trend unlike the cast iron rotors with regions of intermittent hot spot which is detrimental to braking conditions. The finite element simulation analysis results are in good agreement with the actual operating test measurements. In conclusion, it can be said that this composite automotive brake rotor prototype is a novel, energy saving, light weight and eco-friendly brake rotor which is also commercially viable and feasible to replace the existing cast iron brake rotor.